New TOEH+P Framework for the Adoption of Smart Patient Management System Strategies at an IVF (In Vitro Fertilization) Program Provider Hospital in Central Java Province - Paminto Agung Christianto (Universitas Kristen Satya Wacana, 2022)
77.7% of IVF patients have high levels of anxiety. To reduce the level of anxiety of IVF patients, hospitals and IVF patients need an intelligent system for handling IVF patients post embiro transfer. The combination of the TOEH framework and patient variables, the new TOEH+P framework becomes the strategy and indicator of assessing the readiness of the hospital before implementing the smart system.